Series of 4.5S RNAs associated with poly(A)-containing RNAs of rodent cells. - Harada, F (1979)
Uninfected mouse kidney cells and mouse leukemia cells L1210 in cluture contained a series of 4.5S RNAs which was structurally identical to the series of 4.5S RNAs associated with genomic RNAs of murine retroviruses and poly(A)-containing RNAs from virus infected cells. Normal rat kidney cells and baby hamster kidney cells in culture also contained a series of 4.5S RNAs. The strucutre of the 4.5S RNAs from mouse, rat and hamster cells were very similar, but not identical. These 4.5S RNAs were not found in cultured cells of other vertebrates, such as human, monkey, cat, mink, rabbit and chicken cells.